Improving The Inventory Management In A Small And Medium Enterprise (SME) - A Case Study In A Printing Firm In Malaysia - Eunice, Wong Siaw Chui (Universiti Sains Malaysia, 2017)
Today, effective inventory management plays an important role in the success of the organizations in new business environment. Inventory management can therefore be one of the crucial determinants of competitiveness as well as operational performance of small and medium enterprises (SMEs) in inventory intensive manufacturing industries. This study sought to determine the inventory management methods or practices used by a small and medium printing enterprise, located in Miri, Sarawak and to analyze the problems faced in managing inventory, thereby providing suitable recommendations to improve the current inventory management practices. In terms of findings, the study revealed that the printing firm faces the problem of having stocks piling up and understock sometimes. Hence, a traditional approach used to classify inventory into different groups, which is the well-known ABC analysis is proposed to have an efficient control of a variety of inventory items in printing company X. Different inventory control policies can then be applied to different groups. Visual management in warehouse and coding label system are established for inventory items prior to the issue as well. Besides, the inefficient methods to manage the inventory record and procurement of inventory in printing company X are examined. On the basis of the findings, this study investigated the cause of poor inventory management method in the printing firm, and thereby an inventory database system is established in order to improve inventory record accuracy and organization’s efficiency within the firm. In addition, the benefits that will be brought by implementing the proposed solutions in the printing firm are discussed well in this study.